Pengembangan E-LKPD Berbasia Problem Based Learning (PBL) Berbantuan Live-worksheet Pada Materi Keanekaragaman Hayati Pada Kelas X SMA - Ririn Wijayanti; Lilan Dama; Febriyanti (Journal of Science, Technology, and Innovation, 2025)
This study aims to develop an E-LKPD based on Problem Based Learning (PBL) that is suitable for use in teaching biodiversity material to 10th grade high school students. This is a development study based on the ADDIE model, with the development stages limited to implementation through limited-scale trials. The research subjects consisted of 16 10th grade students at a high school in Gorontalo City. The validity of the learning tools was reviewed based on strong theoretical rationale and internal consistency through assessment by media experts, subject matter experts, and practitioners. The validation results showed that the media experts' scores ranged from 86% to 100%, while the subject matter experts' and practitioners' validation scores ranged from 71% to 85%, indicating that the tools were valid and feasible. Practicality was tested through the implementation of learning, student activities, and student responses. The implementation of learning was rated as excellent with a score of 81%–100%, student activities were rated as good with a score of 61%–80%, and student responses were rated as acceptable. The results of the study indicate that PBL-based E-LKPD assisted by live-worksheets is feasible to use and receives positive responses from students.